Evaluation of the efficacy and safety of injectable glycosaminoglycan-peptide complex (GPC) in patients with osteoarthritis: a multicenter observational study GLADIOLUS (GPC in the treatment of osteoarthritis: a follow-up study of pain relief and local symptom reduction) - L. I. Alekseeva; A. E. Karateev; E. Yu. Pogozheva; V. N. Amirdzanova; E. S. Filatova; V. A. Nesterenko (Современная ревматология)
Glycosaminoglycan-peptide complex (GPC) is a popular injectable extended-release symptomatic agent (ERSA) in Russia for the treatment of osteoarthritis (OA). To date, no large-scale studies of GPC used in real clinical practice have been conducted in our country.Objective: to evaluate the efficacy and safety of GPC in the treatment of OA in real clinical practice.Patients and methods. A multicenter observational non-interventional study was performed to evaluate the efficacy of GPC (Rumalon® , a cycle of intramuscular injections thrice weekly; a total of 25 injections). A study group consisted of 2,955 patients (75.4% female) aged 61.4±11.8 years) with knee and hip OA, and generalized OA (GOA) with the previous inefficacy of oral ERSAs, moderate/severe pain, and the need for regular use of nonsteroidal anti-inflammatory drugs (NSAIDs). 414 (14%) patients received a GPC and diacerein combination 100 mg/day. The investigators assessed the dynamics of pain during movement and at rest, functional disorders (on a numeric rating scale (NRS) of 0–10), as well as the need for NSAIDs at 12 weeks after starting the GPC cycle.Results and discussion. 98.5% of the patients completed their GPC treatment cycle. The therapy decreased the intensity of pain at rest from 4 [3; 5] to 1 [0; 2] and during movement from 6 [5; 7] to 2 [1; 3] and reduced the severity of functional disorders from 5 [4; 6] to 1 [0; 3]. The number of patients with a good response to therapy (a≥50% decrease in symptom severity) for pain at rest and during movement was 55.6 and 53.5%, respectively; and for functional disorders was 50.8%. 68.1% of patients stopped taking NSAIDs. The GPC and diacerein combination was more effective than GPC monotherapy: the number of patients with a ≥50% decrease in movement pain was 62.8 and 54.3%, respectively (p <0.001). GPC was well tolerated. During treatment, there were skin allergic reactions (0.3%), moderate injection-site pain (0.37%), and adverse reactions (ARs) related to the gastrointestinal tract (8%) and cardiovascular system (6%) (which were likely to be caused by NSAIDs). There were no serious ARs that were life-threatening and required hospitalization.Conclusion. GPC allows successful control of the main symptoms of knee and hip OA and GOA, by reducing pain, and those of functional disorders, and the need for NSAIDs. The GPC and diacerein combination is more effective than GPC monotherapy. GPC therapy is well tolerated and very rarely causes ARs.